Fractional Radiofrequency Microneedling as a Monotherapy in Acne Scar Management: A Systematic Review of Current Evidence - Niaz G; Ajeebi Y; Alshamrani HM; Khalmurad M; Lee K (Clinical, Cosmetic and Investigational Dermatology)
Ghassan Niaz,1 Yara Ajeebi,2 Hussein M Alshamrani,3 Murad Khalmurad,4 Kachiu Lee5,6 1Department of Internal Medicine, King Faisal Specialist Hospital and Research Center, Jeddah, Saudi Arabia; 2Faculty of Medicine, Jazan University, Jazan, Saudi Arabia; 3Department of Dermatology, King Abdulaziz University, Jeddah, Saudi Arabia; 4Department of Biological Sciences, Fairleigh Dickinson University, Teaneck, NJ, USA; 5Department of Dermatology, Temple University, Philadelphia, PA, USA; 6Main Line Center for Laser Surgery, Ardmore, PA, USACorrespondence: Ghassan Niaz, Department of Internal Medicine, King Faisal Specialist Hospital and Research Center, Ar Rawdah, 2572, Jeddah, 23433, Saudi Arabia, Email ghassanabniaz@gmail.comAbstract: Fractional radiofrequency microneedling (FRM) is a popular, minimally invasive skin rejuvenation modality for treating acne scarring. In this study, we aimed to systematically evaluate the current literature on the efficacy and safety of FRM as a monotherapy to treat different types of facial acne scarring. We systematically reviewed all available literature on FRM techniques used for acne scarring by searching the PubMed and EBSCO databases up to July 2024. 16 studies involving 481 patients, comprising six prospective studies, six randomized clinical trials, three retrospective studies, and one comparative trial, were included. FRM is likely an effective treatment for acne scarring when used as a monotherapy. Further randomized controlled trials are needed to establish appropriate treatment parameters.Keywords: fractional radiofrequency microneedling, monotherapy treatment, acne scarring